Slug (Deroceras sp.) as main disseminating vector of bud rot disease of coconut in southern India - R. ChandraMohanan, K. M. Sharadraj (Journal of Phytology, 2015)
The common slug, Deroceras sp. found abundantly in the coconut gardens during rainy season was observed as a major source of Phytophthora inoculum dispersal vector as its fecal matter contained abundant Phytophthora propagules which cause bud rot disease of coconut in southern states of India. This is the first report of the possible role of Deroceras sp. in the disease cycle as a vector disseminating Phytophthora propagules from India. Microscopic examination of fecal matters of the slugs collected from both healthy and diseased coconut gardens in disease endemic areas revealed the presence of Phytophthora propagules in the faeces of slugs.